2010
DOI: 10.1152/ajpregu.00367.2009
|View full text |Cite|
|
Sign up to set email alerts
|

Overexpression of NGF in mouse urothelium leads to neuronal hyperinnervation, pelvic sensitivity, and changes in urinary bladder function

Abstract: Schnegelsberg B, Sun T, Cain G, Bhattacharya A, Nunn PA, Ford AP, Vizzard MA, Cockayne DA. Overexpression of NGF in mouse urothelium leads to neuronal hyperinnervation, pelvic sensitivity, and changes in urinary bladder function. Am J Physiol Regul Integr Comp Physiol 298: R534 -R547, 2010. First published December 23, 2009; doi:10.1152/ajpregu.00367.2009.-NGF has been suggested to play a role in urinary bladder dysfunction by mediating inflammation, as well as morphological and functional changes, in sensory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
275
2
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(305 citation statements)
references
References 113 publications
22
275
2
4
Order By: Relevance
“…Thus various stimuli can lead to secretion of chemical substances capable of modulating the activity of underlying smooth muscle (141,271), as well as nearby sensory neurons. For example, urothelial-specific overexpression of nerve growth factor (NGF) results in increased bladder nerve "sprouting" and increased voiding frequency (119,251). It has been shown that urothelial-derived NO can be released in response to mechanical as well as chemical stimulation and may either facilitate or inhibit the activity of bladder afferent nerves conveying bladder sensation (18,42).…”
Section: Urothelium-lamina Propria Interactionsmentioning
confidence: 99%
“…Thus various stimuli can lead to secretion of chemical substances capable of modulating the activity of underlying smooth muscle (141,271), as well as nearby sensory neurons. For example, urothelial-specific overexpression of nerve growth factor (NGF) results in increased bladder nerve "sprouting" and increased voiding frequency (119,251). It has been shown that urothelial-derived NO can be released in response to mechanical as well as chemical stimulation and may either facilitate or inhibit the activity of bladder afferent nerves conveying bladder sensation (18,42).…”
Section: Urothelium-lamina Propria Interactionsmentioning
confidence: 99%
“…CRPS pain not only is influenced by peripheral autonomic changes but also by central changes Postganglionic sympathetic neurons might modulate inflammatory reactions, either directly by releasing prostaglandins (Gonzales et al, 1991) or indirectly by releasing NGF from vascular smooth muscle cells (Tuttle et al, 1993) or the bladder (Schnegelsberg et al, 2010). As noted above, the sympathetic nervous system influences innate immunity via dendritic cells, which are modulated by adrenoreceptors: α 1 -adrenoceptors stimulate and β 2 -adrenoceptors inhibit dendritic cell migration and immune system activation (Maestroni, 2006).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Neurotrophins, particularly NGF, are thought to play a role in bladder function (18,20,24,25,29,34,77), and particularly in bladder diseases including IC/BPS (44,50), OAB (37,42) and bladder outlet obstruction (43). NGF exerts pleiotropic effects in the peripheral and central nervous system, regulating sensory and sympathetic neuronal development and maintenance (25,48,61). NGF plays wellestablished roles in urinary bladder inflammation (61,71), most likely contributing to increased voiding frequency (18,20,24,28,33,49,77).…”
Section: Changes In the Inflammatory Milieu Of The Urinary Bladder Afmentioning
confidence: 99%
“…NGF exerts pleiotropic effects in the peripheral and central nervous system, regulating sensory and sympathetic neuronal development and maintenance (25,48,61). NGF plays wellestablished roles in urinary bladder inflammation (61,71), most likely contributing to increased voiding frequency (18,20,24,28,33,49,77). Administration of NGF intravesically (24), intrathecally (76), intramuscularly (77), or via adenovi- Fig.…”
Section: Changes In the Inflammatory Milieu Of The Urinary Bladder Afmentioning
confidence: 99%